The principles of the scientific method: from Hippocrates to Claude Bernard - Cappelletti, Vincenzo (Medicina e Morale, 2024)
Methodological, epistemological, anthropological discourse has always existed in medicine and must have the virtue of being brief and aiming at the self-awareness of the method. The latter is irreplaceable for physicians who, as managers of experience, must then create their own style of thinking and conduct towards theoretical and practical problems.